EVALUATION OF ORGANIZATIONAL PERFORMANCE STRATEGIES - Heydari, Mohammad; Xiaohu, Zhou; Lai, Kin Keung; Yuxi, Zheng (Proceedings of National Aviation University (archive), 2020)
Background: This article seeks to complement the previous literature and clarify the importance of paying attention to the various performance evaluation methods. Also, should be noted in this research, a balanced scorecard is examined. A balanced scorecard model with four dimensions of vital financial, internal processes, customer, and learning and growth, seeks to control short-term operations of the organization with its long-term vision and strategies. Therefore, the organization focuses on key performance ratios within the scope of the goals. Aim: This article seeks to identify the determinants, to find the affect performance assessment of the organization by balanced scorecard method in the performance of the organization. Setting: In this research, a questionnaire has been used that includes 28 questions, and for each balance point card 7 points are considered, it should also be stated that the results are the result of a survey of 60 people. Methods: In this study, Mini-Tab software has been used to calculate the value of z and p-value, and we conclude with a significant level of 0.05 28 questions. So that if it is more than 0.05. The assumption at the significant level is 0.05 = we accept otherwise, and the insurance organization between 10-30 years projects strategic goals. An average of 6 is considered for testing hypotheses. Results: Research hypothesis test results shows that the H1 assumption is accepted. In other words, we can say that all four aspects of the balanced assessment card: financial, customer, internal processes, and the perspective of growth and learning lead to the achievement of the goals of the organization's strategy. Conclusion: Regarding the mentioned cases, it can be said that the insurance company has achieved its goals and the four-way alignment function is appropriate.